Association of geriatric nutritional risk index with all-cause hospital mortality among elderly patients in intensive care unit - Peng, Jiang-Chen; Zhu, Yi-Wei; Xing, Shun-Peng; Li, Wen; Gao, Yuan; Gong, Wen-Wen (Frontiers in Nutrition, 2023)
Background: Malnutrition is associated with poor outcomes for geriatric patients in intensive care unit (ICU). It is important to identify patients at risk of malnutrition and provide individual nutrition support. The assessment of malnutrition risk is not easy for these patients due to their cognitive impairment. Geriatric nutrition risk index (GNRI) is a simple and objective scoring tool to evaluate the risk of malnutrition in elderly patients. In this study, we aimed to see whether GNRI score was appropriate to predict clinical outcomes among geriatric patients in the setting of ICU. Materials and methods: Elderly patients with age ≥ 65 years were extracted from Medical Information Mart for Intensive Care IV (MIMIC-IV) database. Categories based on GNRI were classified as major risk (GNRI < 82), moderate risk (GNRI 82 to < 92), low risk (GNRI 92 to ≤ 98), and no risk (GNRI > 98). The primary outcome was all-cause hospital mortality. Multivariable Cox proportional hazards regression models and restricted cubic spline were used to investigate associations of GNRI with hospital mortality, respectively. A two-piecewise linear regression model was applied to examine the inflection point of GNRI on hospital mortality. To reduce selection bias, propensity score matching (PSM) was used in a 1:1 ratio. Results: A total of 3696 geriatric patients were finally included with median age 75 (69, 81) years. The prevalence of major risk was 28.6%. In the fully adjusted model, GNRI categories featured a negative trend with hospital mortality (P for trend=0.037). Restricted cubic spline analysis demonstrated an L-shaped relationship between GNRI and hospital mortality before and after matching. The inflection point was 78.7. At the left side of inflection point, GNRI levels were significantly negatively associated with hospital mortality (HR=0.96, 95% CI: 0.94-0.98; P<0.001) and featured no significant relations at the right side. Multiple linear regression also showed that GNRI was negatively associated with length of stay in hospital. Conclusions: The major risk of malnutrition defined by GNRI was able to predict poor prognosis for geriatric patients admitted to ICU.